Risk management policies of telecommunication and engineering laboratories - Shah, Abdul Salam; Fayaz, Muhammad; Shah, Asadullah; Shah, Shahnawaz (Science & Engineering Research Support Society (SERSC), 2016)
The Telecommunication laboratories plays an important role in carrying out research in the different fields like Telecommunication, Information Technology, Wireless Sensor Networks, Mobile Networks and many others fields. Every Engineering University has a setup of laboratory for students particularly for PhD. scholars to works on the performance analysis of different Telecommunication Networks including WLANS, 3G/4G, and Long Term Evolution (LTE). The laboratories help students to have hands on practice on the theoretical concepts they have learned during the teaching at the university.The technical subjects have a practical part also which boosts the knowledge of students and learning of new ideas. The Telecommunication and Engineering laboratories are equipped with different electronic equipment's like digital trainers, simulators and some additional supportive devices like computers, air conditioners, projects, and large screens, with power backup facilities that creates the perfect environment for experimentation. The setup of Telecommunication end Engineering laboratories cost huge amount, required to purchase equipment, and maintain the equipment, In any working environment risk factors is involved. To handle and avoid risks there must be risk management policy to tackle with accidents and other damages during working in the laboratory, may it be human or equipment at risk. In this paper, we have proposed a risk management policy for the telecommunication and E engineering laboratories, which can be generalized for similar types of laboratories in engineering fields of studies.